2022
DOI: 10.3389/fonc.2022.1009796
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein sodium in the surgical treatment of pleomorphic xanthoastrocytomas: Results from a retrospective study

Abstract: ObjectivePleomorphic xanthoastrocytoma (PXA) is a rare brain tumor, most commonly affecting children and young adults. Surgical resection represents the mainstay of treatment, and extent of resection is associated with improved survival. In this study, we analyzed the role of sodium fluorescein (SF) in improving intraoperative visualization easing resection.MethodsSurgical database of FLUOCERTUM study (Besta Institute, Milan, Italy) was retrospectively reviewed to find pleomorphic xanthoastrocytomas and anapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Regardless of tumor type, sodium fluorescein demonstrated no significant difference in rate of fluorescence. Out of all studies included in our analysis, all demonstrated fluorescence rates above 77%, and 11 out of 15 demonstrated fluorescence rates > 90% [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Previous prospective cohort studies by Acerbi have shown a high specificity and sensitivity of fluorescein in glioma detection, citing numbers as high as 79.1% and 80.8%, respectively [12].…”
Section: Discussionmentioning
confidence: 86%
“…Regardless of tumor type, sodium fluorescein demonstrated no significant difference in rate of fluorescence. Out of all studies included in our analysis, all demonstrated fluorescence rates above 77%, and 11 out of 15 demonstrated fluorescence rates > 90% [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Previous prospective cohort studies by Acerbi have shown a high specificity and sensitivity of fluorescein in glioma detection, citing numbers as high as 79.1% and 80.8%, respectively [12].…”
Section: Discussionmentioning
confidence: 86%